2013
DOI: 10.3389/fonc.2013.00074
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation in Glioblastoma Initiating Cells

Abstract: Glioblastoma (GBM) is the most common primary malignant brain tumor in adults with a median survival of 12–15 months with treatment consisting of surgical resection followed by ionizing radiation (IR) and chemotherapy. Even aggressive treatment is often palliative due to near universal recurrence. Therapeutic resistance has been linked to a subpopulation of GBM cells with stem cell-like properties termed GBM initiating cells (GICs). Recent efforts have focused on elucidating resistance mechanisms activated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 69 publications
0
30
0
Order By: Relevance
“…In parallel, the development of methods aimed at considering the system as a whole, hence with all its constituents mutually interacting, have become a major topic, involved as a necessary step beyond reductionism limitations6111213. For example, cancer progression involves multiple events and is the result of the interactions with cells of the immune system within the tumor micro-environment1415161718192021.…”
mentioning
confidence: 99%
“…In parallel, the development of methods aimed at considering the system as a whole, hence with all its constituents mutually interacting, have become a major topic, involved as a necessary step beyond reductionism limitations6111213. For example, cancer progression involves multiple events and is the result of the interactions with cells of the immune system within the tumor micro-environment1415161718192021.…”
mentioning
confidence: 99%
“…GICs express stem cell markers, notably PROM1 (CD133), FUT4 (SSEA-1), L1CAM and CD44, and they can also express markers of neurons, astrocytes and oligodendrocytes, suggesting that they can differentiate into all major cell types present in the adult brain. [2][3][4] Consistent with the hypothesis that poor patient survival is linked to the presence of a therapy-resistant cell population in glioblastoma, GICs are resistant to ionizing radiation (IR) 5,6 and to the chemotherapeutic agent temozolomide, 7 both of which are widely used in the clinic as first-line therapy. 1 The resistance has been attributed to enhanced DNA damage checkpoint responses, enhanced repair of damaged DNA and enhanced export of toxic compounds from the cells.…”
mentioning
confidence: 58%
“…1 The resistance has been attributed to enhanced DNA damage checkpoint responses, enhanced repair of damaged DNA and enhanced export of toxic compounds from the cells. [5][6][7] In an article in this issue, Venere et al 8 identified new properties of GICs that can be exploited for more efficient therapies. Specifically, they report that GICs isolated from xenografted human glioblastomas contain high levels of reactive oxygen species (ROS), at least as compared with non-GICs.…”
mentioning
confidence: 99%
“…It is proved that ionizing radiation causes brain tumors in humans. Radiation therapy for ringworm in children has led to a significant and statistically significant increased risk of gliomas, meningiomas and nerve sheath tumors (Rivera et al, 2013). The results of epidemiological studies that have investigated the risk of brain tumors in relation to the X-ray examination of skull and teeth, are contradictory.…”
Section: Discussionmentioning
confidence: 99%